An English Island methodology: didactic strategies for learning English in Italian primary schools - Davide Capperucci; Robert Frank Muzzi; Elena Niccolai (Firenze University Press, 2019)
In Italian primary schools the educational approach to teaching and learning foreign languages must be increasingly centered on the learner and focused on developing the acquisition of demonstrable competences through learning by doing. Based on a sequence of didactic strategies that form the circular learning path and on the association of three coded languages (mime, visual, oral), the methodology An English Island favours learner centered-instruction, as well as the learner's active participation and involvement in creating the mental/physical grooves through which the language flows and turns into long-term memory. This paper focuses on the theoretical and methodological foundations of An English Island supported by a set of practical exercises that describe the educational process in which the teacher becomes the coach, observer, and scaffolder in order to train the citizens of the future.